Negara Adil dan Makmur (Refleksi Filsafat Politik Al-Ghazali) - Ulum, Ahmad Manbaul (State Islamic Institute of Kudus (IAIN Kudus), 2022)
This research is motivated by the geopolitical situation in various countries where in fact there are still many countries that act arbitrarily against their citizens. This article aims to describe Al-Ghazali's political thought which explains about good governance according to Islam, how to be an equitable leader. Then explain in detail about the basics of justice that must be owned by a leader of the State. The method of this research is library research. The primary data is sourced from Al-Ghazali’s book related to political perspective, such as Political Ethics which is a translation of Al-Tibru Al-masbuk Fi Nashihat Al-Muluk. Meanwhile the secondary data is sourced from journals, articles, and documents that related to this research. The result of this research is Al-Ghazali formulated ten principles of justice that must be possessed by a leader, including : recognizing the value of power along with the risks and dangers; the ruler must be happy and like to ask for advice from scholars; moved to eradicate injustice; humble/not arrogant; aware that the ruler/leader is basically also the people; likes to help/cares for the people; qonaah/no luxury; gentle; loves the people; does not violate the shari'ah.